KEPUASAN PASIEN PADA PELAYANAN FISIOTERAPI DI RSUD KOTA KENDARI - Ihsan, Ihsan; Harefa, Karnirius; Yosepha Ginting, Desideria (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
With the increasing number of hospitals in Indonesia, service, professionalism and competence must be at a level that represents service quality. The quality of providing special impetus health services, including physiotherapy services, to understand patient expectations, which in turn can increase patient satisfaction and foster patient loyalty. The purpose of this study was to determine the level of patient satisfaction that is tangible, reliable, responsiveness, assurance, and emphatic at Kendari City Hospital. This study uses a phenomenological method and is qualitative in nature. Focus Group Discussion (FGD) analytical techniques were used in conjunction with observation, interviews, and other data collection methods. The results of the research conducted provide a statement that patient satisfaction with physiotherapy services at the Kendari city hospital has not run optimally. Of the five dimensions of service quality, there are four (4) service dimensions that are not optimal in supporting patient satisfaction. These four things are an uncomfortable waiting room, physiotherapists who don't explain procedures, narrow action rooms, rather long registration times, and fast therapy times.